'J'accuse.!': the continuous failure to address radiophobia and placing radiation in perspective. (1st June 2021) - Lindberg, John C H
Abstract: As far as carcinogens are concerned, radiation is one of the best studied, having been researched for more than 100 years. Yet, radiation remains feared in many contexts as a result of its invisibility, its relationship with cancers and congenital disorders, aided by a variety of heuristics and reinforced by negative imagery. The strong socio-psychological response relating to nuclear energy has made radiation a classical case in the risk literature. This is reflected clearly following the nuclear accidents that have taken place, where the socio-psychological impacts of the clear dissonance between real and perceived health effects due to radiation exposure have caused considerable health detriment, outweighing the actual radiological impacts. Despite considerable efforts to normalise humankind's relationship with radiation, there has been little shift away from the perceived uniqueness of the health risks of radiation. One consistent issue is the failure to place radiation within its proper perspective and context, which has ensured that radiophobia has persisted. The radiation protection community must get better at placing its research within the appropriate perspective and context, something that is far too rarely the case in discussions on radiation matters outside of the scientific community. Each member of the radiation protection community has an ethical, professional and moral obligation to set the record straight, to challenge the misconceptions and factual errors that surround radiation, as well as putting it into the proper perspective and context. Failing to do so, the well-established harms of radiophobia will remain, and the many benefits of nuclear technology risk being withheld.